Genomic characterization of canine circovirus detected in red foxes (Vulpes vulpes) from Italy using a new real-time PCR assay - De Arcangeli S; Balboni A; Kaehler E; Urbani L; Verin R; Battilani M (Journal of Wildlife Diseases, 2020)
Data on canine circovirus circulation among red foxes (Vulpes vulpes) are limited. We report the detection of canine circovirus in a red fox from Italy. The virus was closely related to strains from dogs (Canis lupus familiaris) rather than those from foxes, suggesting a possible transmission between the two species